1977
DOI: 10.1039/p19770000706
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of boldine (1,10-dimethoxy-6aα-aporphine-2,9-diol)

Abstract: The incorporation of (k) -norprotosinomenine, (*) -nororientalhe, (i) -nor-reticuline, and (i) -reticuline into boldine in Litsea glutinosa has been studied, and the specific utilization of the (*) -reticuline demonstrated. The evidence supports the direct oxidative coupling of (+)-reticdine to give isoboldine, which in turn is shown to be a specific precursor of boldine. The plants also converted norboldine into boldine. Double labelling experiments involving the methoxy-groupof (f) -reticuline showed that mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1977
1977
2000
2000

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…We first reexamined the reaction of boldine with Br 2 in acetic acid instead of CCl 4 , assuming that protonation of the nitrogen might hinder the dehydrogenation side reaction, and found that a considerable excess of the halogen was required to achieve high conversions of the alkaloid. Under these conditions, 3,8-dibromoboldine ( 3 ) was obtained in 64% isolated yield, and 3-bromoboldine ( 2 ) in only 9% yield, with chromatographic evidence of the formation of several other products .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We first reexamined the reaction of boldine with Br 2 in acetic acid instead of CCl 4 , assuming that protonation of the nitrogen might hinder the dehydrogenation side reaction, and found that a considerable excess of the halogen was required to achieve high conversions of the alkaloid. Under these conditions, 3,8-dibromoboldine ( 3 ) was obtained in 64% isolated yield, and 3-bromoboldine ( 2 ) in only 9% yield, with chromatographic evidence of the formation of several other products .…”
Section: Resultsmentioning
confidence: 99%
“…3-Bromoboldine (2): light tan needles from C 6 H 6 ; mp 192−194 °C (lit. 208−209 °C); [α] 18 D +88° ( c 0.11, MeOH); 1 H NMR (DMSO- d 6 ) δ 7.81 (1H, s, H-11), 6.75 (1H, s, H-8), 3.78 (3H, s, O- 10-CH 3 ), 3.50 (3H, s, O- 1-CH 3 ), 3.03 (1H, dd, J = 11.5 Hz, J ‘ = 4.3 Hz, H-5α), 2.97 (1H, dd, J = 13.4 Hz, J ‘ = 3.9 Hz, H-7α), 2.83 (1H, dd, J = 13.4 Hz, J ‘ ≈ 3 Hz, H-6a), 2.69 (2H, m, H-4α and H-4β), 2.39 (3H, s, N- CH 3 ), 2.30 (1H, m, H-5β), 2.26 (1H, dd, J = J ‘ = 13.4 Hz, H-7β); 13 C NMR (DMSO- d 6 ) δ 146.7 (C-2), 146.4 (C-10), 146.3 (C-9), 143.2 (C-1), 129.6 (C-7a), 129.0 (C-3a), 127.3 (C-1a), 125.5 (C-1b), 121.9 (C-11a), 115.3 (C-8), 111.6 (C-11), 110.3 (C-3), 62.4 (C-6a), 60.0 ( O- 1-CH 3 ), 55.8 ( O- 10-CH 3 ), 52.7 (C-5), 43.6 ( N- CH 3 ), 33.4 (C-7), 30.5 (C-4); anal. C 56.34%, H 4.98%, N 3.46%, calcd for C 19 H 20 BrNO 4 , C 56.17%, H 4.96%, N 3.46%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of any type of proaporphine leads to consider reticuline as their sole precusor which undergoes an intramolecular ortho-para oxidative coupling according to a well known biogenetic pathway (11). This is supported by feeding experiments on L. glutinosa where such a biosynthesis has been enlighted (12). Here two minor alkaloids do not agree with this mechanism, nonsocorydine 7, resulting of an ortho-ortho coupling of reticuline followed by O-methylation and N-demethylation, and pallidine 10, made from the same precursor by aparapara coupling (13).…”
Section: Mass Spectra Were Recorded On Varianmentioning
confidence: 99%
“…The crude alkaloids were extracted from the roots (75 kg) by previously described procedures (12). Extraction into organic solvents on the basis of differential basicity afforded a number of fractions.…”
Section: Mass Spectra Were Recorded On Varianmentioning
confidence: 99%